Repeated dose budesonide/formoterol compared to salbutamol in adult asthma: a randomised crossover trial. Issue 3 (1st September 2022) - Kearns, Nethmi; Bruce, Pepa; Williams, Mathew; Doppen, Marjan; Black, Melissa; Weatherall, Mark; Beasley, Richard
Background: Our objective was to determine the comparative bronchodilator, systemic β2 -agonist, cardiovascular and adverse effects of salbutamol 200 µg and budesonide/formoterol 200/6 µg when taken repeatedly in stable asthma. Methods: This open-label, crossover, single-centre, controlled trial randomised adults with asthma to different orders of two treatment regimens: salbutamol 200 µg via metered-dose inhaler at 0, 30, 60 and 90 min, then salbutamol 2.5 mg via nebuliser at 120, 140, 160 and 420 min; or budesonide/formoterol 200/6 µg one actuation via Turbuhaler at 0, 30, 60 and 90 min, then two actuations at 120, 140, 160 and 420 min. The primary outcome measure was forced expiratory volume in 1 s (FEV1 ) after 180 min. Secondary outcomes included repeat measures of FEV1, serum potassium, heart rate and adverse events Results: Of 39 patients randomised, two withdrew due to adverse events (QTCF prolongation and T-wave abnormalities) after the first intervention with salbutamol. The mean±sd change from baseline FEV1 180 min after randomisation for salbutamol and budesonide/formoterol regimens was 0.71±0.46 L (n=38) and 0.58±0.45 L (n=37), respectively, with a mean±sd paired difference of −0.10±0.40 L (n=37) and a model-based estimated difference of −0.12 (95% CI −0.25–0.02) L (p=0.088). In the main secondary analysis, salbutamol resulted in significantly greater FEV1 from 30 to 240 min, but lesser FEV1 at 360 and 420 min. Salbutamol resulted in a significantly lower serum potassium, and a higher heart rate and number of adverse events. Conclusions: The comparative bronchodilator responses of repeated administration of salbutamol 200 µg and budesonide/formoterol 200/6 µg differed depending on the time of measurement. Salbutamol caused greater systemic β2 -agonist and cardiovascular effects and more adverse events. The comparative bronchodilator responses of repeated administration of salbutamol 200 µg and budesonide/formoterol 200/6 µg differed depending on the time of measurement; salbutamol caused greater systemic β2 -agonist, cardiovascular and adverse effects https://bit.ly/3KqWcDm